2012
DOI: 10.1002/j.2161-0045.2012.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Existentialism and Super's Life‐Span, Life‐Space Approach

Abstract: As workers face a changing and ever‐complex employment landscape, traditional career theories and approaches may not be sufficient in meeting career challenges. Calls for integrated career theories have emerged as more people seek meaning and purpose in their lives and careers. This article proposes a career counseling option that integrates existentialism and Super's (1990) life‐span, life‐space approach to establish a foundation for a broader approach to career development that views clients holistically by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
0
16
0
3
Order By: Relevance
“…However, the authors believe that tracking graduates' career progress and their perceived career prospect after entering into the industry offers salient insights and reflection upon their choice of degree studied and their future career development. In addition, graduates' real working experiences contribute a lot to faculty's or career counselor's understanding and planning in offering career coaching or counseling intervention (Creed & Blume, 2013;Sterner, 2012;Zikic & Hall, 2009). Career counseling is helpful for potential graduates in better preempting actual working reality and challenges that they face after graduation.…”
Section: Career Prospect and Decision Making Of Htm Graduatesmentioning
confidence: 98%
“…However, the authors believe that tracking graduates' career progress and their perceived career prospect after entering into the industry offers salient insights and reflection upon their choice of degree studied and their future career development. In addition, graduates' real working experiences contribute a lot to faculty's or career counselor's understanding and planning in offering career coaching or counseling intervention (Creed & Blume, 2013;Sterner, 2012;Zikic & Hall, 2009). Career counseling is helpful for potential graduates in better preempting actual working reality and challenges that they face after graduation.…”
Section: Career Prospect and Decision Making Of Htm Graduatesmentioning
confidence: 98%
“…Изучение текучести и отношения к карьере осуществляется в рамках анализа влияния организационных изменений на адаптацию и состояние сотрудника в усложняющейся динамической среде. Такие факторы, как организационная политика, ситуационные ограничения и ролевая перегрузка, уменьшают удовлетворенность работой и увеличивают текучесть [Podsakoff, LePine, LePine, 2007;Sterner, 2012;Baruch, Vardi, 2016]. Соответствие карьерных планов ожиданиям персонала, политике компании и другим контекстным переменным изучается в работах [Sullivan, Baruch, 2009;Kovalenko, Mortelmans, 2014].…”
Section: влияние практик управления человеческими ресурсами на добровunclassified
“…The incorporation of grief and loss issues into the career counseling curriculum could be accomplished by having students analyze case studies and present a career counseling treatment plan that, as suggested by Sterner (2012), integrates current career counseling theories with existential and grief and loss issues. Another approach might include class exercises in client conceptualization that emphasize clients’ primary and secondary losses with regard to unemployment and what appropriate interventions might be applied.…”
Section: Recommendations For Incorporating Grief and Loss Educationmentioning
confidence: 99%